PERCEPTIONS OF INTERDISCIPLINARY CERTIFIED TEACHERS ON THE IMPLEMENTATION OF THE TEACHER CERTIFICATION PROGRAM IN BENGKULU CITY - Reza, Heru Kreshna; Judijanto , Loso; Susanti, Melly (Idaarah: Jurnal Manajemen Pendidikan, 2024)
This study aims to explore the perceptions of interdisciplinary certified teachers towards the implementation of the teacher certification program. This study used a qualitative research design with a multiple case study approach. The sample used was five certified high school teachers from public schools in Bengkulu City. Data collection methods included semi-structured interviews and document analysis of teachers' lesson plans. Thematic analysis was conducted using NVivo 12 software. The findings of this study revealed two main themes that emerged. First, teachers' motivations and expectations regarding the teacher certification program in Indonesia. Second, this study examines the perceived benefits of the program. This research contributes to the evaluation and improvement of the teacher certification program in Indonesia, which can improve the quality of education. The implication of this study is that teachers can report improvements in pedagogical knowledge, curriculum understanding, content knowledge, lesson planning, and teaching performance. From the findings, it can be concluded that the teacher certification program in Indonesia is expected to improve the quality of education in Indonesia.